Edukasi dan Pemberian Informasi Obat Penyakit Asam Urat di Kampung Biru Banjarmasin: Education and Provision of Information on Gout Medication in Kampung Biru Banjarmasin - Rahmawati, Rahmawati; Azhari, Tasya Khairunisa; Hamzah, Hasyrul; Kiromah, Naelaz Zukhruf Wakhidatul; Ismail, Rahmat (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Gout disease, also known as gouty arthritis, is a condition characterized by elevated blood uric acid levels, typically above 7.5 mg/dL. This occurs due to a disruption in purine metabolism that triggers an increase in uric acid. This disease is a degenerative condition that affects the joints and is most commonly found in the community, particularly among the elderly. The implementation of community service was carried out in Kampung Biru, Kampung Melayu sub-district. The number of community service members was 24. The purpose of this community service was to provide education and drug information services, as well as guidance on how to take medication correctly, to increase public awareness about gout and its management. The stages carried out were providing a pre-test, followed by an educational presentation using media in the form of leaflets, health checks, and drug information services provided by the community service team. General practitioners issued prescriptions, and a post-test was subsequently administered. The average results obtained during the pre-test were 3.75, and the post-test results were 4.05. These results indicate an increase in knowledge before and after receiving education, with a positive impact on participants regarding the importance of health awareness.